Plant growth-promoting rhizobacteria: strategies to improve abiotic stresses under sustainable agriculture. (21st July 2019) - Kumar, A.; Patel, J. S.; Meena, V. S.; Ramteke, P. W.
Abstract: The abiotic stresses like drought, heavy metal and salts directly or indirectly influence the global environmental pollution and decrease the agricultural productivity. The stress tolerant plant growth promoting rhizobacteria (PGPR) play an important role against the abiotic stresses in terms of enhancing the efficacy of soil, plant growth promotion (PGP). Stress tolerance PGPRs have certain specific PGP properties such as hormones synthesis, 1-aminocyclopropane-1-carboxylate (ACC) deaminase, Indole-3-acetic acid (IAA) production, Abscisic acid (ABA) synthesis, enzymes production, nitrogen fixation, phosphorus (P) and Potassium (K) solubilization, as results which protect various crops during such stress conditions and consequently enhance crop sustainability. Efficient PGPRs isolated from various stress conditions have certainly, more useful against that particular stress. This article highlighted the isolation of various stresses tolerant PGPRs from varieties of crops under different stress conditions and their effect on varieties of crops to enhance their plant growth promotion.